Fabrication of reliable ZTA composite/Ti6Al4V alloy joints via vacuum brazing method: Microstructural evolution, mechanical properties and residual stress prediction. Issue 7 (July 2021) - Wang, Yifeng; Liu, Manqin; Zhang, Hao; Wen, Zhiru; Chang, Maochun; Feng, Guangjie; Deng, Dean
Graphical abstract: Highlights: Reliable ZTA composite/Ti6Al4V alloy brazing joints were fabricated by Ag-28Cu filler. The microstructure of the joints was characterized in detail. The effects of brazing temperature on the joints were investigated. The possible joining mechanism was discussed. A 3D FE model was established to study the residual stresses in the joints. Abstract: Reliable ZTA composite/Ti6Al4V alloy brazing joints were fabricated by Ag-based filler metal. The microstructural investigation of the joints was conducted in detail. A thin TiO layer formed at the ZrO2 /(Cu, Al)3 Ti3 O interface, whereas the Al2 O3 matrix of the ceramic was found directly contacting with (Cu, Al)3 Ti3 O. The thicknesses of the reaction layers and the diffusion zone increased as the brazing temperature rose, but the Ag(s, s) region became smaller significantly. The joint fabricated at 825 °C had the maximum shear strength of 54 ± 4 MPa. A three dimensional finite element model was established to study the residual stresses in the ZTA composite/Ti6Al4V alloy joints. Relatively large tensile residual stresses in X direction were predicted in the (Cu, Al)3 Ti3 O layer and the Ti-Cu compound region. The simulated maximum tensile residual stress in Z direction of about 190 MPa was on the vertical edges of ZTA near the ZTA/brazing seam interface.